1987
DOI: 10.1038/328814a0
|View full text |Cite
|
Sign up to set email alerts
|

Currents through the fusion pore that forms during exocytosis of a secretory vesicle

Abstract: Exocytosis, or the fusion of cytoplasmic vesicles with the cell membrane, occurs in nearly all eukaryotic cells, but its mechanism is not understood. Morphological and electrophysiological studies have suggested that membrane fusion begins with the formation of a 'fusion pore', a narrow channel across the closely adjacent membranes of vesicle and cell that forms the first connection of the vesicle lumen with the cell exterior and later dilates to allow release of vesicle contents. We used the patch clamp techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
301
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(315 citation statements)
references
References 0 publications
13
301
1
Order By: Relevance
“…The granule fusion event itself is virtually instantaneous in mast cells [23] and in bovine pituitary lactotrophs (Zorec, Sikdar and Mason, manuscript in preparation). The slow time course of Cm increase illustrated in fig.…”
Section: Resultsmentioning
confidence: 99%
“…The granule fusion event itself is virtually instantaneous in mast cells [23] and in bovine pituitary lactotrophs (Zorec, Sikdar and Mason, manuscript in preparation). The slow time course of Cm increase illustrated in fig.…”
Section: Resultsmentioning
confidence: 99%
“…The current carried by ion S through a cylindrical fusion pore of length l and cross-sectional area a is given by (1) where D S is the diffusion coefficient for ion S, z S its valency, [S V ] its intravesicular free concentration and [S E ] its extracellular free concentration. V is the voltage present across the fusion pore and F,R,T have their usual meaning.…”
Section: Electrodiffusion Calculationsmentioning
confidence: 99%
“…Neurotransmitter and hormone release occurs by exocytosis, which begins with the formation of a narrow fusion pore 1,2 . Fusion pores in mast cells and chromaffin cells have typically an initial conductance of ~330 pS 1,3 through which vesicular serotonin and catecholamines are released, respectively 4,5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological measurements of mast cells [23][24][25][26][27] as well as adrenal chromaffin cells [28], suggested the presence of fusion pores at the cell plasma membrane as "dynamic entities", originating following a secretory stimulus [29]. Results from earlier studies on cell capacitance and conductance measurements, suggested that following stimulation of secretion, the "exocytotic fusion pore" abruptly appears as a 1-2 nm in diameter pore at the cell plasma membrane, with conductance similar to a large ion channel [29].…”
Section: Porosome: the Universal Secretion Machinerymentioning
confidence: 99%